Implications of COVID-19 prevention on the occurrence of childhood diarrhea in the Semen Bench district, Bench Sheko zone, southwestern Ethiopia - Bezuayehu Alemayehu; Seblework Mekonen; Argaw Ambleu (Frontiers Media S.A., 2024)
BackgroundCoronavirus (COVID-19) is a virus that occurred in Wuhan, China, in December 2019 and has spread to several countries. Although interventions in water, sanitation, and hygiene (WASH) for COVID-19 are likely a pre-existing response to childhood diarrhea, evidence of the effects of COVID-19 preventative strategies on childhood diarrhea has been lacking. This study aimed to assess the implications of COVID-19 prevention for the occurrence of childhood diarrhea in rural communities of Ethiopia.MethodsA community-based cross-sectional study was conducted from 10 May 2020 to 30 July 2020 involving selected households in the Semen Bench district, Bench Sheko zone, southwestern Ethiopia. A single population proportion formula was used to obtain a total of 768 sample sizes. Data were collected from selected households using a simple random sampling technique. Epidata 3.1 was used to enter the data and then exported to Stata 14 for analysis. Descriptive statistics along with binary and multivariable logistic regression analyses were used to identify factors of COVID-19 knowledge and practices related to childhood diarrhea. The chi-squared test was used to check the association between COVID-19 prevention and childhood diarrhea reduction.ResultsA total of 720 (93.75%) households participated in the study to achieve the study objectives. Approximately 55% of the participants had a good understanding of COVID-19 prevention, while only 48.5% had good COVID-19 prevention practices. The prevalence of childhood diarrhea was 19.3% which was more common among households with poor practices of COVID-19 prevention. The respondents with poor COVID-19 prevention knowledge were 42% (AOR = 0.58, 95% CI: 0.398, 0.847, P = 0.005) less likely to develop childhood diarrhea than those who had good COVID-19 prevention knowledge. Households with poor practices for COVID-19 prevention were 75.1% more likely to develop childhood diarrhea than those who had good preventive practices for COVID-19 prevention (AOR = 1.751, 95% CI: 1.193, 2.571, P = 0.004). The lower risk of childhood diarrhea is significantly related to good COVID-19 prevention practices. However, households with no formal education and a lack of WASH facilities have a higher likelihood of having childhood diarrhea in the household.ConclusionCOVID-19 preventative strategies help reduce the prevalence of diarrhea in children. More research using prospective study designs and advanced statistical models is needed to better understand the implication of COVID-19 preventative efforts in reducing childhood diarrhea.